2011
DOI: 10.1111/j.1399-5448.2010.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered inflammatory, oxidative, and metabolic responses to exercise in pediatric obesity and type 1 diabetes

Abstract: Obesity (Ob) and type 1 diabetes (T1DM) are associated with increased inflammation and oxidative stress, which are major pathogenetic pathways toward higher cardiovascular risks. While long-term exercise protects against systemic inflammation and oxidation, acute exercise actually exerts pro-inflammatory and oxidative effects, prompting the necessity for better defining these molecular processes in at-risk patients; in particular, very little is known regarding obese and T1DM children. We therefore examined ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 44 publications
2
43
0
5
Order By: Relevance
“…An otherwise comparable LGI meal completely prevented rises in these inflammatory cytokines. The clinical relevance of these findings should not be underestimated because offsetting hyperglycemia and inflammation is important for preventing early pathogenic diabetesrelated complications (23). Additionally, b-hydroxybutyrate concentrations did not rise significantly during either condition ( Fig.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…An otherwise comparable LGI meal completely prevented rises in these inflammatory cytokines. The clinical relevance of these findings should not be underestimated because offsetting hyperglycemia and inflammation is important for preventing early pathogenic diabetesrelated complications (23). Additionally, b-hydroxybutyrate concentrations did not rise significantly during either condition ( Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Inversely, consuming HGI foods may promote accelerated muscle glycogen restoration (18,19), reducing the incidence of postexercise hypoglycemia (11,20). However, the need to reduce the insulinto-carbohydrate ratio may be associated with postprandial hyperglycemia following ingestion of HGI foods (15,16), potentially leading to metabolic, hormonal, and inflammatory disturbances (21)(22)(23). The aim of the current study was to examine the influence of the glycemic index (GI) of a meal and subsequent bedtime snack consumed after evening exercise on postprandial glycemia, metabolism, and circulating inflammatory markers in addition to nocturnal glycemic control in type 1 diabetes.…”
mentioning
confidence: 99%
“…Regarding the articles with longitudinal design, it was found that of 14 selected articles, 11 showed effect (decrease or increase) in cardiometabolic markers [18][19][20][21][22][25][26][27] PA intervention programs period ranged from seven weeks 9 to one year 28 . (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…It was found improvement in arterial endothelial function in overweight adolescents. Also using exercise program in ergometer cycle, Rosa et al 26 verified that obese adolescents and adolescents with type one diabetes, there was decrease in IL-6 concentrations and better metabolic control.…”
Section: Articles Identified N = 324mentioning
confidence: 99%
See 1 more Smart Citation